Deactivation of prospective memory intentions: Examining the role of the stimulus–response link. - Streeper, Emily; Bugg, Julie M. (Memory & Cognition, 2021)
Successful prospective remembering involves formation of a stimulus (e.g., bottle of medication and/or place where the bottle is kept)–response (e.g., taking a medication) link. We investigated the role of this link in the deactivation of no-longer-relevant prospective memory intentions, as evidenced by commission error risk. Experiment 1a contrasted two hypotheses of intention deactivation (degree of fulfillment and response frequency) by holding constant the degree of intention fulfillment (e.g., participants responded to one of two target words) while manipulating the number of times the intention was performed. Findings supported the response frequency hypothesis. Experiment 1b employed novel lure trials to examine what "stimulus" participants link the prospective memory response to—target words and/or the salient contextual cue—and compared commission errors to Experiment 1a. Findings suggested the salient context alone does not always function as the stimulus. Collectively these findings, in conjunction with those of Experiment 2 (a within-experiment replication) and a combined analysis, suggest that (a) intention deactivation is facilitated by prior responding (formation/strengthening of stimulus–response links), but additional research is needed to establish the robustness of this effect, and (b) when responding frequently to targets, participants are more likely to bind the response to the context alone than to the target or target/context combination, possibly because they learn to rely on context to predict target occurrence. The latter finding was robust and indicates that deactivation of the appropriate stimulus (target and/or context)–response link may be a critical component of reducing commission errors.